PSA response to cabazitaxel is associated with improved progression-free survival in metastatic castration-resistant prostate cancer: the non-interventional QoLiTime study - Hammerer, Peter; Hofheinz, Ralf-Dieter (World journal of urology, 2018)
To evaluate the association between prostate-specific antigen (PSA) response and progression-free and overall survival in men with metastatic castration-resistant prostate cancer (mCRPC) treated with cabazitaxel.
Gesehen am 16.06.2020